In situ Kinetic study of the limonite phase by X-ray difraction and u-Raman spectroscopy - Palacios, P. R. (2010)
A kinetic study of the limonite phase, FeO(OH)-nH2O, was made through X-ray diffraction and u-Raman spectroscopy. The powder oxide was obtained in the Taraco disctrict, Huancané province in the Puno Region, Peru. The goethite phase was identifed by X-ray diffraction as the main minerogical component, after an in situ heat treatment between 100 and 500ºC in an air oxidizing atmosphere and in an inert nitrogen atmosphere. The goethite phase remains stable in the temperature range from room temperature to 200ºC. Between 200ºC and 250ºC there is a phase transition, x-Fe3+O(OH)-->x-Fe2O3, i.e., the pathway from goethite phase to hematite phase, as shown the evolution of the diffraction profiles, Also, the in situ heat treatment u-Raman spectra corroborate the phase transition at 290ºC though the transformation of the characteristic bands of the goethite phase to hematite phase in the energies range from 200 to 180 cm-1